The Effectiveness of Graphic Organizer Method on Teaching Descriptive Writing at Mambaus Sholihin Junior High School - Saadatuddaroini Saadatuddaroini; Anni Rufaidah (Journal of Education and Religious Studies, 2022)
This study investigated the effect of the Graphic Organizer Method on Teaching Descriptive Writing at First Grade in Mts. Mambaus Sholihin Gresik. The population of this research was the students of first grade of Mts. Mambaus Sholihin used simple random sampling. The research method was pre-Experimental design, which was conducted in one group pre-test post-test. To analyze the data, the researcher used paired sample t-test to determine whether there was significant effect before and after treatment in Experimental class. The result showed that the experimental group scores had a significant difference before being taught the Graphic organizer method or after. That can be known based on the results of the pre-test and post-test. with the comparison of the magnitude of t that we get in the manual counting (t0) = 12,59 and the magnitude of t listed in the table of values (t.ts.5% = 2.03), we can know that t0 is greater than tt .2.03 > 12,59. So it can be concluded that the hypothesis is accepted or Ha is accepted, while Ho is rejected. descriptive writing.